Analysis of Compensation and Work Discipline on Employee Performance at Aneka Jaya Demak 2 Supermarket with Work Motivation as an Intervening Variable - Aviv Risqi Afani; Efriyani Sumastuti; Heri Prabowo (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study analyzes the effect of compensation and work discipline on employee performance with work motivation as an intervening variable at Aneka Jaya Demak 2 Supermarket. A quantitative survey method was applied to 60 employees using saturated sampling, with data analyzed via PLS-SEM. Results show that compensation and work discipline significantly affect both employee performance and work motivation. Work motivation also significantly affects performance and emerges as the strongest factor. Moreover, work motivation mediates the relationship between compensation and work discipline and employee performance. These findings imply that improving performance requires fair compensation, good discipline, and enhanced motivation. Companies should therefore optimize all three factors simultaneously.